First report of two chalcidoids parasitizing arecanut inflorescence caterpillar, Tirathaba mundella Walker (Lepidoptera: Pyralidae) from Karnataka, India - Saneera, E. K.; Mohan, Chandrika; Santhosh, Shreevihar; Thube, Shivaji H. (Journal of Plantation Crops, 2019)
First report of two chalcidoids parasitizing arecanut inflorescence caterpillar, Tirathaba mundella Walker (Lepidoptera: Pyralidae) from Karnataka, India